Video intervention for the psychiatric waiting room: proof-of-concept randomised controlled trial of RESOLVE (Relaxation Exercise, SOLVing problem and cognitive Errors). Issue 5 (September 2019) - Naeem, Farooq; Munshi, Tariq; Gratzer, David; Rodie, David; Irfan, Muhammad; Rao, Sanjay; Husain, Nusrat; Farooq, Saeed; Sanches, Marcos; Ayub, Muhammad; Lecomte, Tania
Abstract : Background: The waiting room in psychiatric services can provide an ideal setting for offering evidence-based psychological interventions that can be delivered through electronic media. Currently, there is no intervention available that have been developed or tested in mental health. Aims: This proof-of-concept study aimed to evaluate a pilot design of RESOLVE (Relaxation Exercise, SOLving problem and cognitiVe Errors) to test the procedure and obtain outcome data to inform future, definitive trials (trial registration at Clinicaltrials.gov NCT02536924, REB Number: PSIY-477-15). Method: Forty participants were enrolled and equally randomised to the intervention, RESOLVE plus treatment as usual arm (TAU), or to a control group (TAU only). Those in the intervention group watched RESOLVE in a room adjacent to the waiting area. Participants in the control received routine care. Outcome measures included the Hospital Anxiety and Depression Scale; the Clinical Outcomes in Routine Evaluations outcome measure; and the World Health Organization Disability Assessment Schedule. These measures were performed by a masked assessor at baseline and at 6-week follow-up. Additionally, we measured the number of contacts with mental health services during the prior 4 weeks. Both intention-to-treat and per protocol analyses were performed. Results: The study proved feasible. We were able to recruit the required number of participants. There was a statistically significant improvement in depression ( P < 0.001), anxiety ( P < 0.001), general psychopathology ( P < 0.001) and disability ( P = 0.0361) in favour of the intervention group. People in the intervention group were less likely to contact the service ( P = 0.012) post-intervention. Conclusions: Findings provide preliminary evidence that evidence-based psychosocial interventions can be delivered through electronic media in a waiting-room setting. The outcome data from this study will be used for future definitive trials. Declaration of interest: None.